2017
DOI: 10.14504/ajr.4.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Seam Properties and Sewability of Crease Resistant Shirt Fabrics

Abstract: The aim of this study was to investigate the effect of crease resistant treatment on sewability and seam properties of cotton shirt fabrics. The effects of the fabric construction (plain, twill, and satin weaves), the concentration of crease resistant chemical, and the stitch density were investigated in terms of seam quality and sewability. Seam efficiency was calculated and the appearance of seams and creases were evaluated using standard methods. Furthermore, the sewability of the fabrics was measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The ATR-FTIR spectrum of DMDHEU treated cotton (without microcapsules) shows additional absorption peaks at 1746 and 1642 cm −1 . These peaks correspond to the C=O bond of ester groups resulting from crosslinking reaction (Figure 6) [18,19]. The peak around 3200-3400 cm −1 was broadened after the grafting of microcapsules.…”
Section: Atr-ftir Resultsmentioning
confidence: 96%
“…The ATR-FTIR spectrum of DMDHEU treated cotton (without microcapsules) shows additional absorption peaks at 1746 and 1642 cm −1 . These peaks correspond to the C=O bond of ester groups resulting from crosslinking reaction (Figure 6) [18,19]. The peak around 3200-3400 cm −1 was broadened after the grafting of microcapsules.…”
Section: Atr-ftir Resultsmentioning
confidence: 96%
“…Seam efficiency is defined as the seam carrying capacity of a fabric itself [17]. Seam efficiency is the ratio between the original and the seamed fabric strength, which is calculated as the ratio of seam strength by fabric tensile strength as presented in Equation (1) [10,11,17,27,36]. The fabric tensile strength was determined using the Strip Method according to ISO 13934-1 standard [42].…”
Section: Seam Efficiencymentioning
confidence: 99%
“…The seam efficiency was calculated using Equation ( 1), which is used to measure the loss in fabric strength caused by needle damage [27]. It is inversely proportional to fabric tensile strength; the high fabric strength lowers the seam efficiency.…”
Section: Seam Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the resistance of threads (structure of fabric) decreases. Illeez et al (2017) investigated the effect of crease-resistant treatment on sewability and seam properties of cotton shirt fabrics. It was found that crease-resistant treatment improved the seam efficiency, sewability and appearance of creases, whereas no positive effect on seam appearance was observed.…”
Section: Parameters Affecting Seam Qualitymentioning
confidence: 99%